International relations intership report: experience at Porto Accounting and Business School’s (Instituto Superior de Contabilidade e Administração do Porto) International Relations Office (GRI) - Laya Alonso, Maria Veronica (2021)
“Versão final (Esta versão contém as críticas e sugestões dos elementos do júri)”